Low-dielectric-loss microwave composite dielectric material for circuit board and preparation method of low-dielectric-loss microwave composite dielectric material

By modifying ZnNb2O6 ceramic powder and PTFE and replacing glass fiber with microfibrous liquid crystal polymer, the problems of insufficient dielectric loss and thermal stability of microwave composite dielectric materials in the prior art are solved, and the effects of continuous adjustable dielectric constant, extremely low dielectric loss and improved thermal stability are achieved.

CN119613898APending Publication Date: 2025-03-14ZHUHAI LONGCHANG CIRCUIT TECH CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411872609.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

It is difficult for existing microwave composite dielectric materials to further reduce dielectric losses and improve thermal stability while maintaining medium and high dielectric constants.

Method used

Modified ZnNb2O6 ceramic powder is used to compound it with PTFE and replace traditional glass fibers with microfibrous liquid crystal polymer (LCP), improving dielectric properties and thermal stability.

Benefits of technology

While maintaining medium and high dielectric constants, extremely low dielectric loss, near zero dielectric constant temperature coefficient, low thermal expansion coefficient and excellent mechanical properties are achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119613898A_ABST
    Figure CN119613898A_ABST
Patent Text Reader

Abstract

The invention discloses a low-dielectric-loss microwave composite dielectric material for a circuit board and a preparation method of the low-dielectric-loss microwave composite dielectric material. The low-dielectric-loss microwave composite dielectric material for the circuit board is prepared from the following raw materials in parts by volume: 40 to 50 parts of polytetrafluoroethylene, 45 to 55 parts of modified ZnNb2O6 ceramic powder and 4.5 to 10 parts of microfibrillar liquid crystal polymer, wherein the modified ZnNb2O6 ceramic powder is obtained by carrying out surface modification on ZnNb2O6 ceramic powder by adopting a compound coupling agent consisting of a silane coupling agent and an organic phosphonic acid modifier. According to the low-dielectric-loss microwave composite dielectric material for the circuit board, the dielectric property is improved by compounding the modified ZnNb2O6 ceramic powder and the PTFE, and the thermal stability is further improved by replacing traditional glass fibers with the microfibrillar liquid crystal polymer; the prepared low-dielectric-loss microwave composite dielectric material for the circuit board has medium and high dielectric constants, and also has extremely low dielectric loss, near-zero dielectric constant temperature coefficient, relatively low thermal expansion coefficient and excellent mechanical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of circuit board materials, and in particular to a low dielectric loss microwave composite dielectric material for circuit boards and a preparation method thereof. Background Art

[0002] Microwave dielectric materials are widely used in high-tech fields such as modern communications, radar, satellites, navigation, and electronic countermeasures. With the rapid development of wireless communication technology, electronic products are constantly being updated and upgraded towards high-frequency and high-speed signal transmission. People have put forward higher requirements for microwave dielectric materials, which has given rise to the market's urgent expectation for higher-performance microwave dielectric materials suitable for circuit boards in high-speed and high-frequency systems.

[0003] Polytetrafluoroethylene (PTFE) has a low dielectric constant and extremely low dielectric loss, stable physical and chemical properties, and is suitable for high-frequency substrate materials. However, the resonant frequency temperature coefficient of PTFE is positive, and the thermal expansion coefficient is large, which is prone to thermal expansion, thermal fatigue and thermal deformation. High-frequency substrates require that the substrate material has low dielectric loss while having excellent other dielectric properties, thermal properties and mechanical properties. Therefore, it is also necessary to improve the dielectric properties, thermal properties and mechanical properties of PTFE composite dielectric materials. Rogers commercial sheet RT / duroid 6006 uses PTFE as the base material. The composite microwave dielectric material produced by it has the characteristics of medium-high dielectric constant and low dielectric loss. The 10GHz dielectric constant is 6.15 and the 10GHz dielectric loss is 0.0027. The product has excellent dielectric properties, but there is still room for the dielectric loss and dielectric constant temperature coefficient to decline. It is necessary to make the dielectric constant temperature coefficient of the composite material close to zero and further reduce the dielectric loss while maintaining the medium-high dielectric constant.

[0004] Therefore, it is urgent to study a composite dielectric material with excellent dielectric properties suitable for high-speed and high-frequency circuit boards. The composite dielectric material has a near-zero dielectric constant temperature coefficient and extremely low dielectric loss while maintaining a medium-high dielectric constant (about 6.5). Summary of the invention

[0005] The purpose of the present invention is to overcome the above-mentioned technical deficiencies, propose a low dielectric loss microwave composite dielectric material for circuit boards and a preparation method thereof, and solve the technical problem in the prior art that microwave composite dielectric materials are difficult to further reduce dielectric loss and improve thermal stability while maintaining medium and high dielectric constants.

[0006] In the first aspect, the present invention provides a low dielectric loss microwave composite dielectric material for circuit boards, wherein the raw materials include, by volume: 40-50 parts of polytetrafluoroethylene, 45-55 parts of modified ZnNb2O6 ceramic powder, and 4.5-10 parts of microfibrous liquid crystal polymer; wherein the modified ZnNb2O6 ceramic powder is obtained by surface-modifying the ZnNb2O6 ceramic powder using a complex coupling agent composed of a silane coupling agent and an organic phosphonic acid modifier.

[0007] In a second aspect, the present invention provides a method for preparing a low dielectric loss microwave composite dielectric material for a circuit board, comprising the following steps: Dispersing the modified ZnNb2O6 ceramic powder, liquid crystal polymer and polytetrafluoroethylene in a second organic solvent and stirring, standing and stratifying after the stirring to remove the supernatant, and then drying to obtain a mixed powder; The mixed powder is crushed and then pressed into a green embryo; The green embryo is sintered to obtain a low dielectric loss microwave composite dielectric material for a circuit board.

[0008] Compared with the prior art, the beneficial effects of the present invention include: The low dielectric loss microwave composite dielectric material for circuit boards of the present invention utilizes modified ZnNb2O6 ceramic powder and PTFE to improve dielectric properties, and utilizes microfibrous liquid crystal polymer (LCP) to replace traditional glass fiber to further improve thermal stability, so that the prepared low dielectric loss microwave composite dielectric material for circuit boards has a medium to high dielectric constant while also having extremely low dielectric loss, near-zero dielectric constant temperature coefficient, low thermal expansion coefficient and excellent mechanical properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0009] Figure 1 This is a scanning electron microscope image of the low dielectric loss microwave composite dielectric material for circuit boards prepared in Example 2 of the present invention. DETAILED DESCRIPTION

[0010] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0011] In the first aspect, the present invention provides a low dielectric loss microwave composite dielectric material for circuit boards, wherein the raw materials include, by volume: 40-50 parts of polytetrafluoroethylene, 45-55 parts of modified ZnNb2O6 ceramic powder, and 4.5-10 parts of microfibrous liquid crystal polymer; wherein the modified ZnNb2O6 ceramic powder is obtained by surface-modifying the ZnNb2O6 ceramic powder using a complex coupling agent composed of a silane coupling agent and an organic phosphonic acid modifier.

[0012] The low dielectric loss microwave composite dielectric material for circuit boards of the present invention can make up for the deficiency of single PTFE by adding modified ZnNb2O6 ceramic powder and liquid crystal polymer into polytetrafluoroethylene (PTFE), so that the dielectric constant of the composite dielectric material finally obtained is between 6.2 and 6.55, and the dielectric loss is between 9.7×10 -4 Below, the temperature coefficient of dielectric constant is close to zero (absolute value is less than 10 ppm / ℃), and the best can reach +2.3 ppm / ℃. Among them, after the surface of ZnNb2O6 ceramic powder is modified by a composite coupling agent composed of silane coupling agent and organic phosphonic acid modifier, the filler has both excellent dispersion characteristics and good surface compatibility with the PTFE matrix, which promotes the improvement of microwave dielectric properties of composite dielectric materials. Microfibrillar liquid crystal polymer replaces traditional glass fiber, which can play a good connecting role between polytetrafluoroethylene and ceramic phase, which is beneficial to improve the overall performance of composite materials.

[0013] In this embodiment, the average particle size of polytetrafluoroethylene is 0.18-0.5 micrometers.

[0014] In this embodiment, the average particle size of the ZnNb2O6 ceramic powder is 0.5-1 micrometer.

[0015] In this embodiment, the microfibrillar liquid crystal polymer is a thermotropic liquid crystal polymer with p-hydroxybenzoic acid (HBA) and 6-hydroxy-2-naphthoic acid (HNA) as the main chain, and further is a type II thermotropic liquid crystal polymer with p-hydroxybenzoic acid (HBA) and 6-hydroxy-2-naphthoic acid (HNA) as the main chain; the molar ratio of HBA / HNA is (2-3):1, preferably 72:27.

[0016] In this embodiment, the average diameter of the microfibrillar liquid crystal polymer is 3-6 micrometers.

[0017] In this embodiment, the silane coupling agent is 3-aminopropyltriethoxysilane (KH550); and the organic phosphonic acid modifier is n-octylphosphonic acid (OPA).

[0018] In this embodiment, the mass ratio of the silane coupling agent to the organic phosphonic acid modifier is 1: (0.5-2), and more preferably 1: 2. Under this ratio, the composite coupling agent has the best modification effect on the ZnNb2O6 particles, and the modified filler particles basically achieve a balance between hydrophilicity and lipophilicity, so that the filler has both excellent dispersion characteristics and good surface compatibility with the PTFE matrix, which promotes the improvement of the microwave dielectric properties of the composite dielectric material.

[0019] In this embodiment, the surface modification process includes: The ZnNb2O6 ceramic powder is dispersed in the first organic solvent and stirred, and then the complex cross-linking agent mixture is added and stirred. After the stirring is completed, the mixture is allowed to stand for stratification and the supernatant is removed. Finally, the modified ZnNb2O6 ceramic powder is obtained by drying.

[0020] The first organic solvent is anhydrous ethanol; the volume ratio of ZnNb2O6 ceramic powder to the first organic solvent is 1:(3-5).

[0021] The preparation process of the compound coupling agent mixture includes: Deionized water, anhydrous ethanol and a silane coupling agent are mixed by ultrasonic treatment, and after the silane coupling agent is hydrolyzed, the mixture is uniformly mixed with organic phosphonic acid modifier powder to obtain a complex coupling agent mixed solution.

[0022] Specifically, the mass ratio of water, anhydrous ethanol and silane coupling agent is (0.8-1.2):(7-9):1, more specifically 1:8:1.

[0023] Specifically, the temperature of ultrasound is room temperature, and the time of ultrasound is 5-10 minutes.

[0024] The amount of the composite cross-linking agent mixture added is 1-2 wt% of the total amount of the ZnNb2O6 ceramic powder, and further 1.5 wt%.

[0025] The mixing and stirring temperature is room temperature, and the mixing and stirring time is 1.5-3h.

[0026] The standing temperature is room temperature, and the standing time is 5-10 minutes.

[0027] The drying temperature is 100-150°C and the drying time is 1-3h.

[0028] In a second aspect, the present invention provides a method for preparing a low dielectric loss microwave composite dielectric material for a circuit board, comprising the following steps: S1, dispersing the modified ZnNb2O6 ceramic powder, liquid crystal polymer and polytetrafluoroethylene in a second organic solvent and stirring, standing and stratifying after the stirring, removing the supernatant, and then drying to obtain a mixed powder; S2, crushing the mixed powder and then pressing it into a green embryo; S3. Sintering the green embryo to obtain a low dielectric loss microwave composite dielectric material for a circuit board.

[0029] In this embodiment, the second organic solvent is anhydrous ethanol.

[0030] In this embodiment, the volume ratio of the second organic solvent to the modified ZnNb2O6 ceramic powder is (3-5):1.

[0031] In this embodiment, the stirring temperature is room temperature, and the stirring time is 1.5-3h.

[0032] In this embodiment, the standing temperature is room temperature, and the standing time is 5-10 minutes.

[0033] In this embodiment, the drying temperature is 100-150° C., and the drying time is 1-3 hours.

[0034] In this embodiment, during the sintering process, the heating rate is 0.5-5°C / min, further 1°C / min, the sintering temperature is 340-370°C, further 370°C, and the sintering time is 4-6h, further 5h. The microwave composite dielectric material of the present invention has a low sintering temperature, which is conducive to reducing production costs and energy consumption, and the preparation method is simple to operate and can be mass-produced.

[0035] In the following Examples 1-4 and Comparative Examples 1-3 of the present invention, to avoid redundancy, the preparation process of the modified ZnNb2O6 ceramic powder is as follows: The ZnNb2O6 ceramic powder was dispersed in anhydrous ethanol and stirred. The volume of anhydrous ethanol was 4 times the volume of ZnNb2O6 ceramic powder. KH550 and APO composite coupling agent mixture was slowly and evenly added thereto. The composite coupling agent mixture was 1.5 wt% of the total amount of ZnNb2O6 ceramic powder. The mixture was stirred for 2 hours. After the stirring, it was allowed to stand for 10 minutes. After stratification, the supernatant was removed and dried to obtain the modified ZnNb2O6 ceramic powder. Among them, the composite coupling agent mixture was obtained by mixing OPA powder with KH550 solution after ultrasonic hydrolysis. The mass ratio of OPA powder to KH550 was 2:1. The silane coupling agent KH550 solution after ultrasonic hydrolysis was a mixture of silane coupling agent KH550, anhydrous ethanol and water. The mass ratio of silane coupling agent KH550, anhydrous ethanol and water was 1:8:1. The ultrasonic time was 5 minutes.

[0036] VECTRA® A950 is a commercially available product, in which the molar ratio of HBA / HNA is 72:27.

[0037] Example 1 First, add 45 parts by volume of modified ZnNb2O6 ceramic powder with an average particle size of 1 micron and 5.5 parts by volume of microfibrous LCP powder (VECTRA® A950) with an average diameter of 5 microns in a beaker, and disperse them in anhydrous ethanol that is 4 times the total volume of the modified ZnNb2O6 ceramic powder. Then, pour 49.5 parts by volume of PTFE with an average particle size of 0.2 microns into the beaker during stirring, continue stirring for 2 hours, let it stand for 5 minutes, remove the supernatant, and obtain a milky white slurry. Then put the slurry into an oven for drying.

[0038] The dried PTFE-based composite material is put into a pulverizer and crushed into fine powder, and the crushed raw material powder is pressed into a cylindrical green embryo with a diameter of 12 mm using a powder tablet press. Finally, the pressed raw material is put into a furnace, and the temperature is slowly increased to 370°C at a rate of 1°C / min. After keeping the temperature for 5 hours, the temperature is naturally lowered to obtain a low dielectric loss microwave composite dielectric material for circuit boards.

[0039] Example 2 First, add 50 parts by volume of modified ZnNb2O6 ceramic powder with an average particle size of 1 micron and 5 parts by volume of microfibrous LCP powder (VECTRA® A950) with an average diameter of 5 microns in a beaker, and disperse them in anhydrous ethanol that is 4 times the total volume of the modified ZnNb2O6 ceramic powder. Then, pour 45 parts by volume of PTFE with an average particle size of 0.2 microns into the beaker during stirring, continue stirring for 2 hours, let it stand for 5 minutes, remove the supernatant, and obtain a milky white slurry. Then put the slurry into an oven for drying.

[0040] The dried PTFE-based composite material is put into a pulverizer and crushed into fine powder, and the crushed raw material powder is pressed into a cylindrical green embryo with a diameter of 12 mm using a powder tablet press. Finally, the pressed raw material is put into a furnace, and the temperature is slowly increased to 370°C at a rate of 1°C / min. After keeping the temperature for 5 hours, the temperature is naturally lowered to obtain a low dielectric loss microwave composite dielectric material for circuit boards.

[0041] Example 3 Compared with Example 2, the only difference is that the content of the ceramic powder in Example 2 is not changed, the contents of PTFE and LCP powder are adjusted to 40 and 10 parts by volume respectively, and other raw materials, method steps and process parameters are the same as those in Example 2.

[0042] Example 4 First, add 55 parts by volume of modified ZnNb2O6 ceramic powder with an average particle size of 1 micron and 4.5 parts by volume of microfibrous LCP powder (VECTRA® A950) with an average diameter of 5 microns in a beaker, and disperse them in anhydrous ethanol that is 4 times the total volume of the modified ZnNb2O6 ceramic powder. Then, pour 40.5 parts by volume of PTFE with an average particle size of 0.2 microns into the beaker during stirring, continue stirring for 2 hours, let it stand for 5 minutes, remove the supernatant, and obtain a milky white slurry. Then put the slurry into an oven for drying.

[0043] The dried PTFE-based composite material is put into a pulverizer and crushed into fine powder, and the crushed raw material powder is pressed into a cylindrical green embryo with a diameter of 12 mm using a powder tablet press. Finally, the pressed raw material is put into a furnace, and the temperature is slowly increased to 370°C at a rate of 1°C / min. After keeping the temperature for 5 hours, the temperature is naturally lowered to obtain a low dielectric loss microwave composite dielectric material for circuit boards.

[0044] Comparative Example 1 Compared with Example 2, the only difference is that the content of LCP in Example 2 is not changed, and the contents of modified ZnNb2O6 ceramic powder and PTFE are adjusted to 40 and 55 parts by volume, respectively.

[0045] Comparative Example 2 Compared with Example 2, the only difference is that the content of LCP in Example 2 is not changed, and the contents of modified ZnNb2O6 ceramic powder and PTFE are adjusted to 60 and 35 parts by volume, respectively.

[0046] Comparative Example 3 Compared with Example 2, the only difference is that the content of the ceramic powder in Example 2 is not changed, and the contents of the PTFE and LCP powders are adjusted to 50 and 0 parts by volume, respectively.

[0047] Comparative Example 4 Compared with Example 2, the only difference is that the surface of the ZnNb2O6 ceramic powder is not modified.

[0048] Comparative Example 5 Compared with Example 2, the only difference is that only OPA coupling agent is used to modify the surface of ZnNb2O6 ceramic powder.

[0049] Comparative Example 6 Compared with Example 2, the only difference is that only KH550 coupling agent is used to modify the surface of ZnNb2O6 ceramic powder.

[0050] Performance Testing The dielectric properties were tested using the parallel plate resonant cavity method according to GB / T 12636-1990 standard.

[0051] The flexural strength is tested according to the ASTM D790 & ISO178 method for determining the flexural properties of plastics.

[0052] The thermal expansion coefficient is tested according to ISO 11359-2-1999 plastic thermodynamic analysis method for the heat deformation temperature of the sample, and the measurement temperature range is 25℃-200℃.

[0053] The thermal conductivity is tested according to the ASTM E 1461-01 flash method for determining thermal diffusivity. The thermal diffusivity of the sample is tested using a NETZSCH LFA-467 laser thermal conductivity analyzer. Before the test, the sample surface needs to be sprayed with graphite.

[0054] The test results are shown in Table 1-2.

[0055] Among them, the scanning electron microscope of the low dielectric loss microwave composite dielectric material for the circuit board prepared in Example 2 is as follows Figure 1 shown.

[0056] Table 1 Performance test results of Examples 1-4

[0057] Table 2 Performance test results of comparative examples 1-6

[0058] Please refer to Table 1. It can be seen from Table 1 that the ceramic filler used in Examples 1-4 of the present invention is in the range of 45-55 vol%, the dielectric constant of the prepared composite dielectric material is between 6.2-6.55, and the dielectric loss is extremely low, at 9.7×10 -4 Below. At the same time The value is within the range of ±9 ppm / ℃, among which, when the ceramic filler ratio is 50 vol%, the The value is +2.3ppm / ℃, reaching the excellent level of this indicator for commercially available microwave dielectric sheets.

[0059] It can be seen from Example 2 of the present invention and Comparative Examples 1-2 that, when the LCP filling amount is the same, as the ZnNb2O6 filling ratio increases, the dielectric constant of the composite material increases, but when the ZnNb2O6 filling ratio is too high, the dielectric loss of the material deteriorates due to the increase in the interfacial polarization strength and water absorption rate of the material.

[0060] It can be seen from Examples 2-3 of the present invention and Comparative Example 3 that, when the filling amount of modified ZnNb2O6 ceramic powder is the same, as the filling ratio of LCP increases, the dielectric loss of the composite material increases but the fluctuation is not large, the temperature coefficient of the dielectric constant increases (from negative to positive), the thermal expansion coefficient decreases, and the thermal conductivity and bending strength increase. However, when the filling ratio is too high, the dielectric constant, thermal properties, and mechanical properties all deteriorate.

[0061] It can be seen from Example 2 and Comparative Example 4 that the compatibility with the PTFE matrix can be improved by surface modification of the ZnNb2O6 ceramic powder, so that the ceramic phase and the PTFE matrix are closely stacked, which is beneficial to improving the dielectric properties, thermal properties and mechanical properties. It can be seen from Example 2 and Comparative Examples 5-6 that the modification effect of the ZnNb2O6 particles using the composite coupling agent of the present invention is better than the modification effect using a single coupling agent. After modification, the filler particles basically achieve a balance of hydrophilicity and lipophilicity, so that the filler has both excellent dispersion characteristics and good surface compatibility with the PTFE matrix. The PTFE-based composite material made of ZnNb2O6 ceramic powder modified by the composite coupling agent has better microwave dielectric properties.

[0062] See also Figure 1 ,pass Figure 1It can be seen that the LCP fiber and PTFE in the composite dielectric material prepared in Example 2 of the present invention have good compatibility and are tightly connected at the interface, which is beneficial to enhancing the dielectric properties, mechanical properties and thermal properties of the composite material.

[0063] In summary, the low dielectric loss microwave composite dielectric material for circuit boards of the present invention uses modified ZnNb2O6 ceramic powder and PTFE to adjust the dielectric constant temperature coefficient to make it close to zero, and uses microfibrillar liquid crystal polymer (LCP) to replace traditional glass fiber to further improve thermal stability, so that the dielectric constant of the prepared low dielectric loss microwave composite dielectric material for circuit boards can be continuously adjusted (6.2-6.55), and the dielectric loss is extremely low, within 9.7×10 -4 Below this temperature, the dielectric constant temperature coefficient is close to zero, and can reach +2.3 ppm / ℃ at best. The thermal expansion coefficient is below 60 ppm / ℃. At the same time, it has excellent mechanical properties. Its performance has reached the level of other commercial polytetrafluoroethylene-based composite dielectric materials. It can be used as a high-frequency and high-speed microwave substrate material in high-frequency microwave system circuit boards.

[0064] The specific implementation of the present invention described above does not constitute a limitation on the protection scope of the present invention. Any other corresponding changes and modifications made based on the technical concept of the present invention should be included in the protection scope of the claims of the present invention.

Claims

1. A low dielectric loss microwave composite dielectric material for a circuit board, characterized in that: The raw materials include, by volume: 40-50 parts of polytetrafluoroethylene, 45-55 parts of modified ZnNb2O6 ceramic powder, and 4.5-10 parts of microfibrillar liquid crystal polymer; wherein, The modified ZnNb2O6 ceramic powder is obtained by surface-modifying the ZnNb2O6 ceramic powder using a composite coupling agent consisting of a silane coupling agent and an organic phosphonic acid modifier.

2. The low dielectric loss microwave composite dielectric material for circuit board according to claim 1, characterized in that: The average particle size of the polytetrafluoroethylene is 0.18-0.5 microns; and / or, The average particle size of the ZnNb2O6 ceramic powder is 0.5-1 micrometer; and / or, The microfibrillar liquid crystal polymer is a thermotropic liquid crystal polymer with p-hydroxybenzoic acid and 6-hydroxy-2-naphthoic acid as main chains; and / or, The average diameter of the microfibrillar liquid crystal polymer is 3-6 microns.

3. The low dielectric loss microwave composite dielectric material for circuit board according to claim 1, characterized in that: The microfibrillar liquid crystal polymer is a type II thermotropic liquid crystal polymer with p-hydroxybenzoic acid and 6-hydroxy-2-naphthoic acid as the main chain, and the molar ratio of the p-hydroxybenzoic acid to the 6-hydroxy-2-naphthoic acid is (2-3):

1.

4. The low dielectric loss microwave composite dielectric material for circuit boards according to claim 1, characterized in that: The silane coupling agent is 3-aminopropyltriethoxysilane; and / or, The organic phosphonic acid modifier is n-octylphosphonic acid; and / or, The mass ratio of the silane coupling agent to the organic phosphonic acid modifier is 1:(0.5-2).

5. The low dielectric loss microwave composite dielectric material for circuit boards according to claim 1, characterized in that: The surface modification process includes: The ZnNb2O6 ceramic powder is dispersed in the first organic solvent and stirred, and then the complex cross-linking agent mixture is added and stirred. After the stirring is completed, the mixture is allowed to stand for stratification and the supernatant is removed. Finally, the modified ZnNb2O6 ceramic powder is obtained by drying.

6. The low dielectric loss microwave composite dielectric material for circuit boards according to claim 5, characterized in that: The first organic solvent is anhydrous ethanol; and / or, The volume ratio of the ZnNb2O6 ceramic powder to the first organic solvent is 1:(3-5); and / or, The amount of the compound cross-linking agent mixture added is 1-2 wt% of the total amount of the ZnNb2O6 ceramic powder; and / or, The mixing and stirring temperature is room temperature, and the mixing and stirring time is 1.5-3h.

7. The low dielectric loss microwave composite dielectric material for circuit boards according to claim 5, characterized in that: The preparation process of the compound coupling agent mixture comprises: Deionized water, anhydrous ethanol and silane coupling agent are mixed by ultrasonic treatment, and after the silane coupling agent is hydrolyzed, it is mixed evenly with an organic phosphonic acid modifier to obtain a complex coupling agent mixed solution; wherein, The mass ratio of the water, the anhydrous ethanol and the silane coupling agent is (0.8-1.2): (7-9): 1; and / or, The temperature of the ultrasound is room temperature, and the time of the ultrasound is 5-10 minutes.

8. A method for preparing a low dielectric loss microwave composite dielectric material for a circuit board as claimed in any one of claims 1 to 7, characterized in that: The following steps are involved: Dispersing the modified ZnNb2O6 ceramic powder, liquid crystal polymer and polytetrafluoroethylene in a second organic solvent and stirring, standing and stratifying after the stirring to remove the supernatant, and then drying to obtain a mixed powder; The mixed powder is crushed and then pressed into a green embryo; The green embryo is sintered to obtain a low dielectric loss microwave composite dielectric material for a circuit board.

9. The method for preparing the low dielectric loss microwave composite dielectric material for circuit boards according to claim 8, characterized in that: The second organic solvent is anhydrous ethanol; The volume ratio of the second organic solvent to the modified ZnNb2O6 ceramic powder is (3-5):

1.

10. The method for preparing the low dielectric loss microwave composite dielectric material for circuit boards according to claim 8, characterized in that: The stirring temperature is room temperature, and the stirring time is 1.5-3h; and / or, During the sintering process, the heating rate is 0.5-5°C / min, the sintering temperature is 340-370°C, and the sintering time is 4-6h.

Citation Information

Cited By

  • High-strength compression-resistant polytetrafluoroethylene material and preparation method thereof

    CN121064583A

  • High-strength compression-resistant polytetrafluoroethylene material and method for producing the same

    CN121064583B